Development of social skills through personal coaching - Giraldo Alegre, Danitza Magaly (2021)
This research was carried to establish the level of development of social skills through personal coaching in students of the tenth cycle students of the School of Linguistics of Santiago Antunez de Mayolo National University in 2019. According to this, the experimental and quantitative method consisted of seven sessions to 35 students from the experimental group. These sessions were based on the most important needs of the students. A control group was considered to which no personal coaching session was applied. A survey was used as an instrument. The results allowed establishing that there is a positive development of skills through personal coaching.